Coral Larvae Every Day: Leptastrea purpurea, a Brooding Species That Could Accelerate Coral Research - Nietzer, Samuel; Moeller, Mareen; Kitamura, Makoto; Schupp, Peter J. (Frontiers in Marine Science, 2018)
Sexually produced larvae are used in various fields of coral research. Because the vast majority of scleractinians reproduces only on one or few occasions per year and ex-situ spawning induction is still very hard to achieve, high efforts are required to obtain planula larvae. Brooding corals have been used to harvest planulae, but the larvae oftentimes differ in various traits, e.g. settlement behavior, from most spawning corals. Other cnidarians, such as Aiptasia spp., have been substituting scleractinians in many aspects of coral research. However, organisms such as Aiptasia differ strongly from scleractinians limiting the transferability of obtained results. This study examines the potential of Leptastrea purpurea as a reliable source of larvae for coral research. Larval output throughout the year as well as settlement behavior of planulae was investigated. Our results show that L. purpurea allows permanent access to planula larvae. The settlement behavior of L. purpurea is similar to many spawning species which increases the transferability of conclusions. We discuss the aptitude of L. purpurea for research on scleractinian physiology, ecology and larval settlement and conclude that L. purpurea is a well-suited organism to accelerate progress in many fields of coral research.